Transracial Adoption, Memory, and Mobile, Processual Identity in Jackie Kay’s Red Dust Road - Ahokas Pirjo (Switzerland, 2025)
Representations of adoptions tend to concentrate on normatively conceived forms of identity, which prioritize the genetic lineage of adoptees. In contrast, scholarship on autobiographical writing emphasizes that identities are not fixed but are always in process and intersectional because they are formed in within inequal power relations. Kay’s experimental, autobiographical narrative Red Dust Road (2010) tackles the themes of adoption, the search for close relatives, and reunion. Many scholars of her autobiographical writings describe the fluidity of the diasporic adoptee identities created by her. My aim is more specific: I examine what I call Kay’s continuously mobile, processual identity construction as a transracial adoptee in Red Dust Road. I argue that her identity formation, which is also intersectional, is interconnected with her multidirectional networks of attachments and the experimental form of her adoption narrative. In addition to an intersectional approach and autobiographical studies, I draw on insights from adoption studies. In my reading of Kay’s work, I pay special attention to the inequalities derived from the intersecting vectors of adoption and race, which also intersect with other dimensions of difference, such as nation, gender, class, and sexual orientation. I employ the notion of the multidirectional in the sense in which McLeod applies it to the study of adoption writing. As I demonstrate, multidirectionality and the complex form of Red Dust Road provide versatile means of conveying Kay’s fragmented acts of memory, which assist her ongoing mobile, processual identity construction. Her multidirectional lines of transformative attachments finally bond her to her adoptive and biogenetic families as well as other affective connections. While Kay’s socially significant narrative indicates, amongst other adoption issues, that transracial adoptions can be successful, it is significant that it has no closure. The last chapter gestures toward potential new beginnings, which indicates that the story of adoption has no end.